The needs of students in learning English in the Faculty of Medicine, Dehasen University of Bengkulu - Pradana, Ami; Sembiring, Lina Tri Astuty Beru (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
The English language course offered in the Faculty of Medicine of DehasenUniversity of Bengkulu was not based on the needs of the students. This can lead to a lack of student motivation and participation in the course. The purpose of this study was to find out the basic needs of medical students in learning English. Finding out the needs of students in the English language course was done with a questionnaire for 36 students of the Faculty of Medicine. The results showed that 18 respondents (50%) stated that they needed English to develop their career, complete their studies and expand international relations. 18 respondents (50%) stated that they need speaking and reading skills for their future career. In addition, twenty-seven (75%) respondents explained that they needed research-related material.